Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepercayaan Calon Pekerja Migran Indonesia Dengan Perceived Value Sebagai Variabel Intervening: Studi Kasus Pada LPK Bahana Inspirasi Muda - Fahira, Luwisca; Syahputra, Syahputra; Madiawati, Putu Nina (Journal of Industrial Engineering & Management Research, 2025)
Migrant workers play a role as foreign exchange heroes, and the government continues to strive to improve services and protections for them through supportive policies. The demand for labor abroad, especially in Japan, is increasing, creating opportunities for training institutions (LPK) such as Bahana Inspirasi Muda to prepare prospective workers. However, challenges arise regarding the trust of prospective workers in recruitment agencies, which is influenced by the quality of service and promotions conducted. This research aims to explore the impact of service quality and promotion on the trust of prospective migrant workers, as well as the role of perceived value as an intervening variable. The study was conducted at LPK Bahana Inspirasi Muda with 134 respondents who are prospective migrant workers. The method used is quantitative with a Structural Equation Modeling (SEM) - Partial Least Squares (PLS) approach. The results show that service quality and promotion have a positive and significant impact on trust. Additionally, perceived value also serves as a mediator that strengthens the influence of both variables on trust. These findings are expected to contribute to the development of policies and practices in the protection of migrant workers in Indonesia.